Imaging of adult intestinal failure. Issue 8 (August 2019) - Smith, J.; Godfrey, E.; Bowden, D.; Hickman, K.; Sharkey, L.; Butler, A.; Upponi, S.
Abstract : Intestinal failure is the inability to maintain adequate nutrition or hydration through the gut. It is caused by a diverse range of benign and malignant aetiologies. Imaging takes a central role in the multidisciplinary assessment of patients with intestinal failure.